PENGETAHUAN DAN SIKAP PEKERJA SEKS KOMERSIAL TENTANG PENYAKIT MENULAR SEKSUAL DI LOKALISASI BANGUNSARI SURABAYA - Mardiansari Wahyu Graha Wijaya (Poltekkes Kemenkes Surabaya, 2013)
Surabaya City Health Department (2010) noted that Health Centers located in red-lightregions have indicated highest number of cases of sexually transmitted diseases (STDs).Increased risk of STD spreading relates to behavioral factors such as of the sex workers andtheir partners, reluctance to seek proper treatment, self treatment and incomplete treatmentprotocol. The purpose of this study was to determine the level of applied knowledge andattitudes relating to STDs among commercial sex workers in Bangunsari red-light zone in2012.This research was meant as a descriptive study, where data were collected throughobservation and interviews. The population under study was as many as 255 commercial sexworkers in Bangunsari red-light zone and a sample of 72 sex workers were drawn bysystematic random sampling. Data processing was carried out on the variables usingappropriate computer program set for descriptive analysis.Respondents' level of applied knowledge on Sexually Transmitted Diseases were'good', represented by 34 (47%) respondents, 'fair' represented by 30 (42%) respondents.Their knowledge are influenced by the level of their education, access to media informationand intervention by health workers. With regard to their attitude toward Sexually TransmittedDiseases, commercial sex workers (CSWs) were 'good' as indicated by 67 (93%) respondents,some of them were 'fair' indicated by 4% respondents. Their attitude are influenced by thelevel of their education, access to media information, regular health examination, awareness tostop their occupation knowing the high-risk of the sex workers and the role of health workers.It is recommended that health workers keep up their positive activities such asteaching and training, building on repondents existing skills to encourage commercial sexworkers to improve their knowledge and skills and to leave their present occupation. Effortsshould be made to improve media information on Sexually Transmitted Diseases (STDs) suchas the provision of counseling or pamphlets / leaflets / brochures on a more regular basis andto encourage commercial sex workers (CSW) to be in touch with local health cadres to keep uptheir motivation toward improved health.Keywords : knowledge/ attitude/ commercial sex workers/ Sexually Transmitted Diseases